State as a constitutional rights holder - Bartoň, Michal (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The article deals with the issue of constitutional rights bearers, especially with the issue of whether the state or any other public authority can be the bearer (holder) of the constitutional rights. The Constitutional Court of the Czech Republic admits that the state can claim constitutional rights if it does not act as a public authority but as a legal person of private law.